Analyzing the Perceptions of Students, Lecturers, and Staff in Understanding the Buddhist Motto: Excellence and Character in Higher Education Management - Syah, Rahmat; Budiwinarto, Arif; Bariboon, Gumpanat (Edukasi, 2024)
This study aims to explore the perceptions and understandings of students, lecturers, and staff about the meaning of the "Buddhist, Excellent, and Characterful" motto. Additionally, the study seeks to determine whether there are differences in perception among these three groups towards the effectiveness of implementing this motto in enhancing educational quality and campus productivity. In this context, an analysis of the perception differences between students, lecturers, and staff is conducted to ascertain the similarities or differences in their perceptions and understandings of the motto's meaning and its implementation effectiveness in a higher education context. This research will also provide insights into the perceptions of students, lecturers, and staff towards the application of the "Buddhist, Excellent, and Characterful" motto within the campus environment. The research design uses a mixed-method approach with the Sequential exploratory design, which is a mixed research design that begins with a qualitative phase followed by a quantitative phase in a sequential manner. The analysis of the "Buddhist, Excellent, and Characterful" motto at STABN Sriwijaya shows a positive perception, particularly from students, with varied perceptions among lecturers. ANOVA testing indicates significant differences between students, lecturers, and staff in their understanding and application of these values. Open responses suggest the need for a more pragmatic and measurable approach in applying these values, as well as the need for increased socialization, the creation of clear indicators, and the practical elaboration of these values. It is crucial for STABN Sriwijaya to develop strategies that support the effective integration of these values into institutional policies and decisions.